Caracterização química inorgânica de rejeitos segregados de serragem de rochas ornamentais do Espírito Santo - Freitas, José Júlio Garcia de (2008)
Industrial wastes of ornamental rocks are in prominence due to the enormous environmental impact generated as result of the large volumes of material generated from sawdust of rock blocks. In waste management, the characterization stage is important and that guides attitudes to be taken in the destination. The present work whished an inorganic chemical characterization of residue from ornamental stones sector sawdust, sampling from a segregated, which was the collection of samples directly at the disposal of sawdust looms, after the hydrocyclone of it and before being mixed in the tank sewage. For each sample collected were obtained in the laboratory values of pH analysis, moisture content, solid content of wet and dry. The samples were subjected to tests of solubilization and leaching, as the series of standards methods for solid waste NBR 10,004, 10,005, 10,006 and 10,007, both from 2004, by ABNT. The segregated wastes were also subjected to the test for total dissolution for determination of some metals of interest. The extracts generated in the test for leaching, solubilization and total dissolution were analyzed by the technique of atomic absorption (F-AAS and GF-AAS) for determination of some metals of interest. For some samples was performed the analysis X-ray diffraction to research the mineralogical composition of the material segregated, and generate possible correlations with the extracts obtained after solubilization and leaching test. There were also conducted some thermal analysis (TG and DTG) with the aim of evaluating possible interactions of the materials inputs used with the powder of some of the rocks sawn. For wastes there was the possibility of forecasting the volume of sludge generated by the abrasive size of the quantity of materials used and volume of rock processed. The process of cutting granite presented uniform water consumption (44,3% ± 6,0), however it was more expensive than the same process for marbles because of the higher consumption of input materials related to the greater hardness of the granite. The TG and DTG showed consistent results on the amount of input CaO during the process of sawing, representing (0,5-1,2)% of the samples. A great solubilization of these metals was found through good correlations obtained between total Cr and Al in terms of the high pH values of the original samples. It was proved through the X-ray diffraction, the presence of Al in major mineral components of rocks and the reason for the dark tone (biotite) from some mother- ix generating rock samples PSG, PF, PA and VP. This efficiency was not repeated in investigating the possible generator of Cr soluble minerals in the samples ASF, AI and ASC. For the material carbonates, it was confirmed in the diffraction graph, the presence of Ca,MgCO3, CaMg(CO3)2 and CaCO3. Through pH analysis and metals determination (Na, Cr, Al, Cd, Pb, Mn, Zn, Fe, Cu, Ca and As) by the technique of atomic absorption in the extracts obtained, it could be classified as dangerous samples (Class I) (pH> 12.5) (ASF, AI, PA, OITA, ASC and JG) Class II (not dangerous and not inert) (CA and PSG) and Class B (not dangerous but inert) (CC, GN, PVC, BR, MBC and SMO).